ANESTEZJOLOGIA I INTENSYWNA TERAPIAThe influence of endobronchial intubation using various muscle relaxant agents on chosen haemodynamic and respiratory parameters - Misiołek, Hanna; Tombarkiewicz, Marek; Rutkowska, Katarzyna; Podwińska, Ewa (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Background: The growing number of non-depolarizing relaxants available in clinical practice is due to the constant search for an ideal intubation agent which could replace suxamethonium chloride, being withdrawn from routine use due to contraindications to its administration. That became a basis for undertaking research aimed at a comparative evaluation of: chosen ventilation and haemodynamic parameters during endobronchial, intubation, performed using various muscle relaxant agents. Material and Methods: The conducted research had prospective and randomized character and was carried out by means of a double blind probe. 3 groups of patients were distinguished, anesthetized with one lung ventilation, using the Robertshaw tube. Group I – recuronium was used for the muscle relaxation in 1.0 mg/kg–1 dose, and infusion was continued with 5-10 mcg/kg/ min–1. Group II – cisatracurium was used for the muscle relaxation in 0.1 mg/kg–1 dose, and then infusion 1-1.5 mcg/kg/min–1. Group III – suxamethonium chloride was used for the muscle relaxation in 1.5 mg/kg–1, after previous precurarization with a non-depolarizing drug, pancuronium, which was then used in IV infusion. Anaesthetic technique and dosing of the remaining general anaesthetics in all groups were standardized. The following parameters were analyzed: initial demographic data, heart rate frequency, systolic blood pressure and central venous pressure in determined time intervals, presence of heart rate disorder/ arrhythmia during laryngoscopy and after intubation, expiratory values of CO2, peak pressure values in respiratory tract, mean respiratory pressure and plateau pressure in determined time intervals. Results: In demographic parameters the studied groups were homogeneous. In 21% of patients in group P a bronchospasm was noted after a performed intubation, which was a significantly greater percentage in comparison to other groups. A significant difference in mean respiratory pressure values in the 5th minute of ventilation of both lungs was noted among the groups. A comparative study between the respiratory pressure values and ETCO2 values indicated a significant positive correlation of both these parameters in the 5th minute of TLV ventilation and in the 15th minute of OLV ventilation only in group P. Conclusion: The examined relaxants (recuronium, cisatracurium and suxamethonium chloride) provide appropriate and comparable haemodynamic conditions. The use of suxamethonium chloride for the purpose of endobronchial intubation performance causes an increase of airway obturation. That indirectly results in worse CO2 elimination.